Financing Economic Development in the Face of Fiscal Constraints: Fiscal Sustainability Measures and Inflation Dynamics in Nigeria - Muhammad, Aliyu (Al-Makki Publisher, 2025)
This study explores the effect of fiscal sustainability measures on inflation in Nigeria, given the fiscal challenges facing the country. The objective of the study is to analyze how fiscal sustainability measures, such as debt-to-GDP ratio and debt service-to-income ratio, affect inflation. The methodology used includes analysis of annual data from 1980 to 2020 using Autoregressive Distributed Lag (ARDL) approach and impulse response function. The results show that debt-to-GDP ratio and debt service-to-export ratio have a significant negative effect on inflation, while debt service-to-income ratio, debt-to-export ratio, and exchange rate have a significant positive effect. This study also finds that inflation responds negatively to shocks from the debt-to-GDP ratio, debt service to exports, and exchange rate, while responding positively to shocks from the debt service to income ratio and debt service to exports ratio. In conclusion, it is important for the debt management office and the ministry of finance to reduce the debt service-to-income ratio and improve fiscal sustainability policies to stabilize inflation in Nigeria.